2010
DOI: 10.1002/bit.22781
|View full text |Cite
|
Sign up to set email alerts
|

Effect of inducible co‐overexpression of protein disulfide isomerase and endoplasmic reticulum oxidoreductase on the specific antibody productivity of recombinant Chinese hamster ovary cells

Abstract: To enhance specific antibody (Ab) productivity (q(Ab)) of recombinant Chinese hamster ovary (rCHO) cells, post-translational limitations in the endoplasmic reticulum during antibody production should be relieved. Previously, we reported that overexpression of protein disulfide isomerase (PDI), which catalyzes disulfide bond exchanges and assists in protein folding of newly synthesized proteins, enhanced q(Ab) of rCHO cells by about 27% (Mohan et al., 2007, Biotechnol Bioeng 98:611-615) . Since the rate limitin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 44 publications
0
24
0
Order By: Relevance
“…For example, effects obtained from TGE are sometimes transferable to a SGE context (Tastanova et al, 2015) and sometimes not (Mohan and Lee, 2010). The need for validation is obviously a drawback of the TGE, SEE and IE platforms.…”
Section: Clonality and Clonal Variationmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, effects obtained from TGE are sometimes transferable to a SGE context (Tastanova et al, 2015) and sometimes not (Mohan and Lee, 2010). The need for validation is obviously a drawback of the TGE, SEE and IE platforms.…”
Section: Clonality and Clonal Variationmentioning
confidence: 99%
“…1). Several reports have demonstrated synergistic effects on the volumetric productivity or q p of co-expressing multiple genes in CHO cells (Cain et al, 2013;Le Fourn et al, 2014;Mohan and Lee, 2010;Peng and Fussenegger, 2009), demonstrating the potential of combining effector genes. In addition to effector gene overexpression, downregulating endogenous genes might be equally important for increasing q p (Feichtinger et al, 2016;Harreither et al, 2015).…”
Section: Concluding Remarks and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overexpression of protein disulfide-isomerase even decreased target protein secretion [87]. Later it was found that the oxidative state of PDI is important for activity and an expression system for inducible coexpression of PDI was devised [88].…”
Section: Engineering Approaches Aimed At Improving Protein Secretion mentioning
confidence: 98%
“…Particular targets investigated to date with a view to improving qP in mammalian cell lines include anti-apoptotic genes [10], [11], [12], [13], cell cycle related genes [14], [15], [16], the folding and assembly machinery in the endoplasmic reticulum [17], [18], [19], [20], [21], [22], and the translational [23], [24], [25] and secretory machinery [26]. However, such approaches to improving qP in mammalian cell lines have largely resulted in conflicting or disappointing results.…”
Section: Introductionmentioning
confidence: 99%